Computer Information Systems and Industrial Management : 14th IFIP TC 8 International Conference, CISIM 2015, Warsaw, Poland, September 24-26, 2015, Proceedings - Saeed, Khalid; Homenda, Wladyslaw; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the proceedings of the 14th IFIP TC 8 International Conference on Computer Information Systems and Industrial Management, CISIM 2015, held in Warsaw, Poland, in September 2015. The 47 papers presented in this volume were carefully reviewed and selected from about 80 submissions. The main topics covered are biometrics, security systems, multimedia, classification and clustering with applications, and industrial management. .
Algorithms -- Biometrics and Biometrics Applications -- Data analysis and Information Retrieval -- Modelling and Optimization -- Pattern Recognition and Image Processing -- Various Aspects of Computer Security -- Various Aspects of Computer Security.
Keywords: Computer science; Optical pattern recognition; Computer software; Computer simulation; Computer Applications; Information Systems Applications (incl. Internet).; Pattern Recognition; Algorithm Analysis and Problem Complexity; Simulation and Modeling